PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING PADA MATERI HIDROLISIS GARAM UNTUK KELAS XI SMA/MA - Handayani, Tiara (Journal of Technique Research (JTR), 2019)
Hydrolysis of salt is a part of chemistry lessons taught at second grade of Senior High School in semester II. The characteristic of the lessons are about the nature of salt based on its acid-base structure, calculation, practice and to find the hydrolyzed salt.  The purposes of this research are to develop Problem Based Learning student worksheet and determine its validity and practicality. This research using a 4-D models, there are 4 stage i.e: 1) define, 2) design, 3) develop, 4) disseminate and limited to develop stage. Instruments of research are validity and practicality given to the lecturers of chemistry department in FMIPA UNP, chemistry teachers and students in SMAN 2 Gunung Talang. The result of this research was analyzed with kappa cohen formula. The validity questionnaire analysis by lecturers and teachers obtains 0.89 point of kappa moment with a very high category of validity. While the practicality questionnaire of teachers and students gets a very high practicality category with each 0.98 and 0.90 point of kappa moment.